Integration of Local Wisdom and Modern Policies: The Role of Traditional Village Government in the Implementation of Sasi in Maluku - Soselisa, Pieter S.; Alhamid, Rugayah; Rahanra, Ivonny Y. (Baileo: Jurnal Sosial Humaniora, 2024)
This study explores the role of traditional village governments in integrating local wisdom with modern policies through the implementation of sasi, a customary natural resource management system in Negeri Lima, Leihitu District, Maluku. Using a qualitative approach, data were collected through observation and in-depth interviews with local stakeholders, including customary leaders and government representatives. The findings reveal that traditional institutions, particularly the kewang, function as critical intermediaries that align indigenous practices with contemporary governance frameworks. The implementation of sasi has become more adaptive and structured due to this synergy, resulting in improved management of local resources such as nutmeg and coconut, while maintaining ecological sustainability and economic relevance. The study highlights that traditional village governments are not merely preservers of custom, but also agents of innovation who mediate change without sacrificing cultural identity. The novelty of this research lies in its focus on the evolving role of adat-based governance in responding to modern challenges, offering a new perspective on how traditional systems can collaborate with formal policies to produce sustainable, locally rooted solutions. This integration model not only reinforces the relevance of local wisdom in contemporary contexts but also presents a replicable framework for similar communities confronting ecological and developmental pressures. The study contributes to social sciences and humanities by providing empirical evidence of how tradition and modernity can co-create responsive, innovative models for natural resource governance.